PENERAPAN PENDEKATAN SCIENTIFIC PADA MATERI BANGUN RUANG SISI DATAR KELAS VIII DI SMP NEGERI 9 PALEMBANG - Permatasari, Ranni; Putri, Ratu Ilma Indra; Indaryanti (Mathematics Education Journal, 2013)
This research aimed to get an overview of the students’ learning result in polyhedral subject through a scientific approach of VIII.11 students in SMP 9 Palembang. Scientific approach is an approach in which students were invited to perform the process of searching the knowledge, to find their own facts, to construct the knowledge, the concepts, and the new values which are necessary for life. This research was descriptive. The results showed that the learning activities using a scientific approach to the polyhedral subject categorized into good with a percentage of 77,46% and the learning result for students’ attitude mastery achieved 70,37%, the learning result for the students’ performance skills mastery achieved 77,78%, and the results of learning for the students’ knowledge mastery achieved 92,59% of 27 students. It can be concluded that the results of learning by using a scientific approach was categorized into good category in learning in terms of the students’ attitudes, skills and knowledge mastery. DOI: https://doi.org/10.22342/jpm.7.1.4649.